Reflection uponcommunication in the period of globalisation - Brychtová, Šárka (Univerzita Pardubice, 2007)
The progres in the sphere of information technology belongs among the most important conditions that have enabled the creation and development of global financial markets and economic globalisation. The globalisation era thus enhances technological capacities for human communication. The mankind has better means of communication than ever before, however even this aspect of globalisation is not accepted unambigously. Authors has paid attention to certain ambivalence of this issue, considering clearly positive as well as negative aspects. The article is drawn up rather as a reflection upon the issue and has no ambition to encompas it as a whole - the authors only reflect upon some parts of the topic and outline them.

The progres in the sphere of information technology belongs among the most important conditions that have enabled the creation and development of global financial markets and economic globalisation. The globalisation era thus enhances technological capacities for human communication. The mankind has better means of communication than ever before, however even this aspect of globalisation is not accepted unambigously. Authors has paid attention to certain ambivalence of this issue, considering clearly positive as well as negative aspects. The article is drawn up rather as a reflection upon the issue and has no ambition to encompas it as a whole - the authors only reflect upon some parts of the topic and outline them.
Keywords: globalizace; Komunikace; komunikační technologie; Internet; Média; komunikační poruchy